Understanding the Link: Parental Communication Quality and JuvenileÂ Delinquency - Aditya Kusumahadi; Sugiariyanti Sugiariyanti (Educational Psychology Journal, 2023)
Adolescence is a turbulent time. This period is the search for self identity, as well as the period in which they deal with the more complex issues of both problems associated with itself or a problem with the environment. Hope every teenager course is to resolve the problem well with others or to the environment. Juvenile delinquency is happening is a form of problem solving using a negative way. Communication in the family works to build the concept of self-actualization and happiness of family members so that family communication has a great influence on the development of adolescent personality. Therefore, this study was to determine the relationship between the quality of communication between children and parents with juvenile delinquency behavior. This research is a quantitative correlation method. This research was conducted at SMK N 3 Salatiga. The sampling technique used is Proportionate Stratified Random Sampling. , The data were taken using a scale of quality of communication with the 54-item has validity coefficients between 0.000 up to 0.024 with a reliability that is entered in the high category amounted to 0.959. While the juvenile delinquency questionnaire with 10 items that has a validity coefficient between 0.000 to 0.018 with a reliability of 0.620. The results obtained in this study are the relationship between the quality of communication of children and parents with juvenile delinquency behavior with a value of -0223, which means that the relationship between the quality of communication of children and parents with juvenile delinquency behavior has a negative relationship, if the quality of children's communication and parents increases, the more negative the behavior of juvenile delinquency.